Tumor Targeting via Integrin Ligands - Marelli, Udaya Kiran; Rechenmacher, Florian; Sobahi, Tariq Rashad Ali; Mas-Moruno, Carles; Kessler, Horst (Frontiers in Oncology, 2013)
Selective and targeted delivery of drugs to tumors is a major challenge for an effective cancer therapy and also to overcome the side effects associated with current treatments. Overexpression of various receptors on tumor cells is a characteristic structural and biochemical aspect of tumors and distinguishes them from physiologically normal cells. This abnormal feature is therefore suitable for selectively directing anticancer molecules to tumors by using ligands that can preferentially recognize such receptors. Several subtypes of integrin receptors that are crucial for cell adhesion, cell signaling, cell viability and motility have been shown to have an upregulated expression on cancer cells. Thus, ligands that recognize specific integrin subtypes represent excellent candidates to be conjugated to drugs or drug carrier systems and be targeted to tumors. In this regard, integrins recognizing the RGD cell adhesive sequence have been extensively targeted for tumor specific drug delivery. Here we review key recent examples on the presentation of RGD-based integrin ligands by means of distinct drug delivery systems, and discuss the prospects of such therapies to specifically target tumor cells.